Insurance Premium And Economic Performance In Nigeria: A Variance Decomposition Approach - Uruakpa, Peter C. (Archives of Business Research, 2019)
This study assessed insurance premium and Nigeria’s economic performance. It aimed at finding out the relationship insurance premium, investment and assets have with Nigeria’s GDP. Descriptive statistics, Augmented Dickey Fuller Unit Root Test, Johansen cointegration, OLS regression, variance decomposition and granger causality tests were adopted. Findings revealed that all the series are significant and but not normally distributed. The correlation matrix shows that there is high and positive correlation between the independent variables. The results of the unit root tests using Augmented Dickey-Fuller test show that all the variables do not have unit roots (that is, are stationary) at 5% in their first differences. The Johansen co-integration result confirms that there is long run relationship between insurance activities and economic growth in Nigeria. The OLS result suggests that 93.11 percent of the total variation found in GDP is explained by the presence of total assets, investments and premium of the insurance industry sector while the F-Statistics has a value of 163.1080 which is highly significant at 5% confidence level implying that insurance industry play significant role in development of the Nigerian economy. The Variance Decomposition for 10 period indicates that Insurance sector investment is more significant than premium for most of the periods. However, since premium represents revenue for the insurance industry it has positive impact on GDP for all the periods while GDP responds positively. This granger causality result shows that there is granger causality relationship between insurance premium, investment and assets have granger causality with GDP. From the findings, it recommends that insurance business authorities should review its reform policy and ensure that policies that will strengthen premium mobilization in Nigeria are put in place. Insurance companies need to invest more of their funds in productive sectors of the economy.